KARAKTERISTIK SIFAT ORGANOLEPTIK KERUPUK KEMPLANG DARI LIMBAH TULANG IKAN TENGGIRI (SCOMBEROMORUS COMMERSONI) DENGAN PERBANDINGAN YANG BERBEDA - Avin Septia; Helmi Haris; Fitra Mulya Jaya (Universitas Djuanda, 2020)
The utilization of mackerel bones as a material for processing crackers becomes a source of protein and calcium in cracker products, so that the cracker products do not only have high nutritional value. This research was conducted from June to July, at the Pempek Cek Aat household industry. The organoleptic test took place at the Fishery Product Processing Technology Workshop, Faculty of Fisheries, PGRI University, Palembang. This study used a completely randomized design (CRD) with 5 levels of treatment. The treatment in this study was the utilization of pangolin fish bone waste in the processing of kemplang crackers. The results of the kemplang cracker favorite test showed that the addition of the concentration of K0 (0%) fish bones and mackerel bone crackers which still had an organoleptic level that was not significantly different was K1 (25%) mackerel bones, because they could still be accepted by panelists. Kata kunci: utilization, fish bones, kemplang